KRIMINALISASI SOSIOLOGIS NIKAH SIRI - Iwan Zaenul Fuad; Agus Fakhrina; Abdul Azis; Ahmad Rosyid (Jurnal Penelitian, 2011)
However, Nikah Siri (unregistered marital) has been seen asa part of the social behavior, and lived in Indonesian society. Thisbehavior often impact living condition of social structure. In anotherside, this social problem must be fixed with appropriate law-makingsystem. The Act Plan of â€œHukum Peradilan Agama Bidang Perkawinanâ€(RUU HPABP) was noted in commitment to criminalize the behavior.Some sounds of pro and anti toward this Act Plan nowadays, makethis issues more interesting be reseacrhed. Applying symbolicinteractionism approach and labelling theory, this study examined thecriminalization issues on the Act Plan in social framework. The frameworkis critical to assume the effectiveness of law making processbased on people participation. This research took place in PekalonganDistrict (the City and Regency of Pekalongan), which is noted for theâ€˜hiddenâ€™ large number of nikah siri practices. Results of the study revealedthe social criminalization of Nikah Siri akin to kinds of peopleâ€™sperception toward the behavior. The hidden types of Nikah Siri(hidden from peopleâ€™s knowledge) had an effect on social constructionto criminalize the behavior, but not the open one